2009
DOI: 10.1103/physrevlett.103.143001
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Cooling Rates of Freely Decaying Fullerenes

Abstract: The cooling rates of C60- have been measured in an electrostatic storage ring between several hundred mus and several tens of ms with one-photon laser excitation. The absolute energy scale is established by the photon energy, and the cooling time interval is derived from the nonexponential decay of the ensemble of hot molecules. The energy decreases due to the combined action of depletion and thermal emission of IR photons with a total energy loss rate that varies inversely proportional to time, 0.9 eV/t. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Indeed, using A elec = 15.7 × 10 6 s -1 , the theoretical values calculated using Eq. (12) gives the best fit of the experimental data as shown in Fig. 13.…”
Section: Theoretical Model: Electronic Fluorescence Emissionmentioning
confidence: 87%
See 1 more Smart Citation
“…Indeed, using A elec = 15.7 × 10 6 s -1 , the theoretical values calculated using Eq. (12) gives the best fit of the experimental data as shown in Fig. 13.…”
Section: Theoretical Model: Electronic Fluorescence Emissionmentioning
confidence: 87%
“…In more recent * chen@univ-lyon1.fr works on this small PAH molecule, the fast radiative decay rate of the anthracene cation was measured [8] and calculations of its structure and spectral properties were performed [9]. A similar radiative decay process has been referred to as fluorescence from thermally excited electronic states in studies on large molecules such as fullerenes [10][11][12] and on small cluster anions Al n − (n = 4-5) [13,14]. Studies on small carbonaceous anions, namely, C 5 − , C 6 − , C 6 H − , and C 7 − , have demonstrated the dramatic effect of the electronic structure on radiative cooling, which was found to be limited to IR emission in the case of C 5 − and C 6 H − and much faster for the other species due to the fluorescence from electronic states [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The cooling measured in these experiments is in general the sum of radiative cooling and depletion by the spontaneous decay intrinsic to the powerlaw decay, radiatively quenched or not. The absolute cooling curve of such a study on C − 60 [74] is shown in Fig. 13.…”
Section: mentioning
confidence: 99%
“…These ions typically exhibit thermionic emission with a rate following an inverse-time (1/t) law, which has been attributed to a very broad population of vibrational states [1] produced in the employed "hot" ion sources. Recent measurements using electrostatic storage devices [5], however, have observed a stronger power-law exponent [6], decay-rate changes due to buffer gas cooling [7], as well as the quenching of the 1/t decay at later times due to radiative cooling [3,8], which has also been theoretically investigated [9]; consequently, this thermionic decay leaves many facets to be investigated. These decays offer the opportunity to explore the competing relaxation channels of fragmentation, radiative cooling, and, in the case of anions, electron emission as reviewed by Andersen et al [10].…”
Section: Introductionmentioning
confidence: 99%